(untitled) (Medico Legal Update, 2020)
Polycystic ovary syndrome (PCOS) is the most public hormonal chaos and the causesthe infertility in the women of reproductive age, offering a varied set of clinical parameters.Irisin had assumed to have a duty in metabolic conditions and PCOS. However, the correlation between irisin and metabolic conditions in PCOS is not clear.The purpose of this control cases study was to evaluate the plasma levels of Irisin in women with overweight PCOS and its correlations with other phenotypes parameters of PCOS. The study involved 90 PCOS women and 40 control healthy women. The PCOS womenwere diagnostic by BMI as overweight. Statistical analysis was performed by using by the SAS (2012) program1.Chiefresults measure was to determinethe plasma Irisin levels in overweight cases. In addition, some phenotypic and anthropometric parametersincluding BMI, lipid profile, sex hormones, FBG, Insulin, and HOMA-IRhad measured in groups of the study. Results offasting Irisin levels showed significantly elevated differences in overweight PCOS women as compared to the levels in overweight control women(P<0.047).The plasma Irisin levels in overweight PCOS womenshowed significantly positively correlated with BMI,FBG, HOMAIR, FSH,lipid profile except HDLc and LH/FSH ratioexhibited significantly negatively correlated (P<0.01). Even though there is as until now no proof for a causal association between irisin andPCOS, it is potential that the alterations in Irisin concentrations maybe considered as a phenotype parameter for the diagnosis or development of PCOS, and may act a new PCOS test to follow this syndrome under diverse management of treatments.